Gamifying place, reimagining publicness: The heterotopic inscriptions of Pokémon Go - WOODS, Orlando (Institutional Knowledge at Singapore Management University, 2020)
This paper explores the transformative effects of augmented reality mobile games on society and space. By layering playfulness onto public space through a digital interface, augmented reality mobile games create a pervasive sense of play that can be accessed by players potentially anywhere, and at any time. Games like these can therefore be understood as heterotopic inscriptions on otherwise mundane environments. Since being released in 2016, Pokémon Go has become one of the most popular augmented reality games in the world. It gamifies place by embedding digital objects within public spaces; in doing so, it can bring about a reimagination of publicness by incentivising players to engage with places – and with each other – in ways that are structured by the competitive logics of play. Through an empirical examination of the playing of Pokémon Go in Singapore, I consider how the game gives rise to new modalities of emplaced meaning, new ways of navigating the city, and increasingly public performances of private play. To conclude, I suggest that research continue to explore the gamifying effects of digital technologies on everyday life.